Peran Ekspresi Gen Pr-1 (Pathogenesis Related Proteins-1) dalam Resistensi Tanaman dan Implikasinya pada Bioteknologi Pertanian - Nia Febrianti; Dian Dwi Lestari; Yusminah Hala (Jurnal Biosilampari : Jurnal Biologi, 2025)
The pr-1 gene is a gene that encodes the PR-1 (Pathogenesis-Related 1) protein which plays a role in the plant defense response to pathogen infection. Although the role of the pr-1 gene as a defense protein has been known, the specific mechanism of how pr-1 responds to various types of pathogens in various plants is still poorly studied in various studies. Therefore, an in-depth analysis is needed regarding the role of the pr-1 gene in plant resistance. This study aims to determine the role of pr-1 (Pathogenesis Associated Proteins-1) gene expression on plant resistance and its implications for agricultural biotechnology. The research method used is a literature study with a qualitative approach. The results of the literature findings were then analyzed descriptively to determine the role of the pr-1 gene in the plant defense response. The findings show that the main role of the pr-1 gene is as a plant defense system against biotic and abiotic environmental threats. The plant resistance mechanism carried out by the PR-1 Protein will be active if there is PAMP/MAMP detection received by the plant cell surface receptor PRR (Pattern Recognition Receptors) to carry out the function of gene expression in plant organs.